2023
DOI: 10.3389/fendo.2023.1153205
|View full text |Cite
|
Sign up to set email alerts
|

The association between total bile acid and bone mineral density among patients with type 2 diabetes

Abstract: ObjectiveBile acids have underlying protective effects on bones structure. Long-term diabetes also causes skeletal disorders including osteoporosis, Charcot arthropathy and renal osteodystrophy. Nevertheless, few studies have reported whether bile acid is associated with bone metabolism in diabetics. This study aimed to explore the relationship between total bile acid (TBA) and bone mineral density (BMD) among patients with type 2 diabetes mellitus (T2DM).MethodsWe retrospectively included 1,701 T2DM patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Notably, emerging evidence suggests bilirubin may confer protective vascular and neurological effects via antioxidant, anti-inflammatory and endothelial function improving mechanisms. [47][48][49] Our results demonstrating an association between higher serum bilirubin levels and favorable outcomes in diabetic stroke patients are consistent with these reports. Furthermore, our study provides novel evidence that bilirubin could potentially serve as a prognostic biomarker specifically in the high-risk diabetic population.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, emerging evidence suggests bilirubin may confer protective vascular and neurological effects via antioxidant, anti-inflammatory and endothelial function improving mechanisms. [47][48][49] Our results demonstrating an association between higher serum bilirubin levels and favorable outcomes in diabetic stroke patients are consistent with these reports. Furthermore, our study provides novel evidence that bilirubin could potentially serve as a prognostic biomarker specifically in the high-risk diabetic population.…”
Section: Discussionsupporting
confidence: 91%
“…Some scientists claimed that BAs enhanced osteoblastic differentiation through binding with Farnesoid X receptor 42 and serum BA levels have been proved to have a positive correlation with BMD in postmenopausal women 43 . However, some researchers argued that BAs are risking factors of osteoporosis in primary sclerosing cholangitis (PSC), type 2 diabetes 44,45 . While our research marks a significant stride in this direction, the intricate mechanisms through which BAs affect bone and muscle health, particularly under IBS‐induced stress, remain elusive.…”
Section: Discussionmentioning
confidence: 83%
“… 43 However, some researchers argued that BAs are risking factors of osteoporosis in primary sclerosing cholangitis (PSC), type 2 diabetes. 44 , 45 While our research marks a significant stride in this direction, the intricate mechanisms through which BAs affect bone and muscle health, particularly under IBS‐induced stress, remain elusive. This knowledge gap signifies the need for extensive future studies focusing on the systemic roles of BAs and the underlying molecular crosstalk in the gut‐musculoskeletal axis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Bile acids are important nutritional sensors and metabolic integrators, which are important substances for regulating bile acid biosynthesis, lipid and glucose homeostasis, and immune signaling, and play a key role in maintaining metabolic homeostasis. 19,20 Population studies have found that bile acids have a potential protective effect on the bone structure in type 2 diabetes patients and postmenopausal women, 21,22 but the specific mechanism is still unclear. Bile acids are signaling molecules that mainly regulate the metabolic status through the nuclear farnesoid X receptor (FXR) and G-protein coupled receptor 5 (TGR5).…”
Section: Introductionmentioning
confidence: 99%